Heat acclimation improves exercise performance - Lorenzo, S.; Halliwill, J. R.; Sawka, M. N.; Minson, C. T. (Journal of Applied Physiology, 2010)
This study examined the impact of heat acclimation on improving exercise performance in cool and hot environments. Twelve trained cyclists performed tests of maximal aerobic power (VO2max), time-trial performance, and lactate threshold, in both cool [13°C, 30% relative humidity (RH)] and hot (38°C, 30% RH) environments before and after a 10-day heat acclimation (~50% VO2max in 40°C) program. The hot and cool condition VO2max and lactate threshold tests were both preceded by either warm (41°C) water or thermoneutral (34°C) water immersion to induce hyperthermia (0.8-1.0°C) or sustain normothermia, respectively. Eight matched control subjects completed the same exercise tests in the same environments before and after 10 days of identical exercise in a cool (13°C) environment. Heat acclimation increased VO2max by 5% in cool (66.8 ± 2.1 vs. 70.2 ± 2.3 ml·kg(-1)·min(-1), P = 0.004) and by 8% in hot (55.1 ± 2.5 vs. 59.6 ± 2.0 ml·kg(-1)·min(-1), P = 0.007) conditions. Heat acclimation improved time-trial performance by 6% in cool (879.8 ± 48.5 vs. 934.7 ± 50.9 kJ, P = 0.005) and by 8% in hot (718.7 ± 42.3 vs. 776.2 ± 50.9 kJ, P = 0.014) conditions. Heat acclimation increased power output at lactate threshold by 5% in cool (3.88 ± 0.82 vs. 4.09 ± 0.76 W/kg, P = 0.002) and by 5% in hot (3.45 ± 0.80 vs. 3.60 ± 0.79 W/kg, P < 0.001) conditions. Heat acclimation increased plasma volume (6.5 ± 1.5%) and maximal cardiac output in cool and hot conditions (9.1 ± 3.4% and 4.5 ± 4.6%, respectively). The control group had no changes in VO2max, time-trial performance, lactate threshold, or any physiological parameters. These data demonstrate that heat acclimation improves aerobic exercise performance in temperate-cool conditions and provide the scientific basis for employing heat acclimation to augment physical training programs.